2016
DOI: 10.5152/balkanmedj.2016.151304
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and Anti-apoptotic Effect of Valproic Acid and Doxycycline Independent from MMP Inhibition in Early Radiation Damage

Abstract: Background: Matrix metalloproteinase (MMP) inhibitors decrease inflammation in normal tissues and suppress cancer progress in normal tissues. Valproic acid (VA) and doxycycline (DX) are MMP inhibitors that have radio-protective effects. Their ability to inhibit MMPs in irradiated tissue is unknown and the role of MMPs in radio-protective effects has not been tested to date. Aims: The purpose of this study was to examine whether administration of VA and DX to rats before irradiation affects tissue inflammation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…We detected 2 distinct MMP-13 bands of 59 and 46 kDa (Figure 2E), which correspond to proMMP-13 (60 kDa) and active MMP-13 (48 kDa) (19). Previously, we reported that despite using rh-proMMP-2 and rh-proMMP-7 for gelatin and casein zymography, active forms of the recombinant proenzymes could be also observed (20). These results indicate that the commercial rh-proMMPs probably contain low amounts of other forms of MMPs that could be detected by highly sensitive zymographic techniques.…”
Section: Resultsmentioning
confidence: 99%
“…We detected 2 distinct MMP-13 bands of 59 and 46 kDa (Figure 2E), which correspond to proMMP-13 (60 kDa) and active MMP-13 (48 kDa) (19). Previously, we reported that despite using rh-proMMP-2 and rh-proMMP-7 for gelatin and casein zymography, active forms of the recombinant proenzymes could be also observed (20). These results indicate that the commercial rh-proMMPs probably contain low amounts of other forms of MMPs that could be detected by highly sensitive zymographic techniques.…”
Section: Resultsmentioning
confidence: 99%